GAMBARAN SIKAP PERAWAT MENGENAI NURSING EARLY WARNING SCORING SYSTEM (NEWSS) DI RUANG RAWAT INAP - Herny " Engeline; Gamya Tri Utami; Jumaini " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Deaths in hospitals due to poor quality of care including negligence in monitoring the patient's condition, medical diagnosis errors or errors in treatment. Nursing Early Warning Scoring System (NEWSS) is a tool that commonly used to detect deteriorating condition of inpatients in medical surgical units to assess vital signs before patients experienced any critical condition. This study aims to determine the attitude of the nurses towards early signs of deterioration of the patients. This is a descriptive research using cross sectional approach. Research samples were 40 of all of the nurses working in the inpatient ward at RSUD Petala Bumi Pekanbaru.Measuring instrument used a questionnaire which give a picture of the demographics of nurses and nurses’ attitude regarding NEWSS. This research used univariate analysis. The results showed 23 respondents (57.5%) have a positive attitude, while 17 respondents (42.5%) have a negative attitude about NEWSS. It is expected that following this research, nurses have a positive attitude about how to detect signs of deterioration conditions of inpatients by recognizing changes in the patients’ vital signs.Keywords: Inpatients, Nursing Early Warning Scoring System, attitude